Fabrication of black silicon via reactive ion etching through Cu micromask. (1st May 2014) - Jiang, Ye; Shen, Honglie; Yue, Zhihao; Wang, Wei; Jin, Jiale
Abstract : Black silicon was fabricated on a pyramid silicon surface via reactive ion etching (RIE) through a Cu micromask formed by a sputtering and annealing process. This adopted RIE technique does not rely on oxygen gas avoiding the silicon surface damage from oxygen plasma. Scanning electron microscopy and an UV–vis‐NIR spectrophotometer were used to characterise the morphology and optical reflectance of the prepared samples with porous structures on a pyramid. The results show that the homogeneity of the Cu micromask controlled by the annealing condition determines the reflectance of the textured silicon wafer. A lowest reflectance of 6.2% appears in the samples with sputtered Cu thin film annealed at a temperature of 500°C for 10 min. This work may provide a choice to fabricate black silicon with an excellent light confinement structure, which will have potential application for the improvement of efficiency of silicon solar cells.